Connective Financing - Chinese Infrastructure Projects and the Diffusion of Economic Activity in Developing Countries - Richard Bluhm; Axel Dreher; Andreas Fuchs; Bradley C. Parks; Austin M. Strange; Michael J. Tierney (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper studies the causal effect of transport infrastructure on the spatial concentration of economic activity. Leveraging a new global dataset of geo-located Chinese government-financed projects over the period from 2000 to 2014 together with measures of spatial inequality based on remotely-sensed data, we analyse the effects of transport projects on the spatial distribution of economic activity within and between regions in a large number of developing countries. We find that Chinese-financed transportation projects reduce spatial concentration within but not between regions. In line with land use theory, we document a range of results which are consistent with a relocation of activity from city centers to their immediate periphery. Transport projects decentralize activity particularly strongly in regions that are more urbanized, located closer to the coast, and less developed. .
Keywords: F15; F35; R11; R12; P33; O18; O19; 330; transport costs; infrastructure; development finance; foreign aid; spatial concentration China